The Problem of Syllabification in Consonant Cluster for English Department Students - Rahmah Widya Sari (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
The focus of this study is an attempt to identify the students of English department problem in syllabifying English consonant cluster. Syllable is the smallest unit beyond single consonants and vowels. Syllabification refers to the division of a word into syllables. Meanwhile, consonant clusters are the combinations of consonant found at the beginning or end of words and syllables. In this research, the researcher used quantitative approach which the design is the descriptive design. The process of collecting data was done by applying the essay test. The test was conducted to 11 respondents from the English department students of IAIN Langsa. According to the result of the essay test, the researcher found that there were three aspects of the students of English department problem in syllabifying English consonant cluster, these were syllabification, consonant cluster and syllable components. There were 45,45 % of students who got mistakes in aspect syllabification and syllable components and 54,55 % of students who got mistakes in aspect syllabification, consonant cluster and syllable components. According to the result of the research, the researcher suggested to the English department students of IAIN langsa have to improve their learning strategy in order to help them in comprehending the syllabification and the syllable structure. In addition, the English department students should enrich their comprehension about syllabification, consonant cluster, syllable components and recognize each of them in the word.